Law Enforcement Against Violence (Engenrichting) - Aniksya Nabila Safikoh; Rida Arantika (AT-TAFAHUM: Journal of Law, 2019)
Indonesia is one of the largest archipelagic countries in the world and a country based on the rule of law. This means that all aspects of life within the territory of the Republic of Indonesia must be based on law. This is in accordance with Article 1 paragraph (3) of the 1945 Constitution of the Republic of Indonesia. Therefore, everything, including vigilance operations, must be carried out in accordance with the provisions that have been made. Mob violence, also known as vigilantism (Engenrichting), is an arbitrary act carried out by individuals or groups who commit acts of violence or abuse against someone known to have committed an unlawful act without being handled through the existing legal process. Criminal prosecution of those who commit acts of violence and abuse is an unlawful act that must be handled according to existing laws and regulations. In fact, legal norms serve as guidelines for every individual to relate to the law in living in society and the nation. In reality, criminal prosecution related to vigilantism, including in Articles 170 and 351 of the Criminal Code, has not been reflected. Scientists have used normative legal research methods, namely by using data obtained from existing sources and data obtained directly as well as two additional data from the results of interviews with two legal experts. The results of the study are explained as follows: (a) Criminal prosecution of vigilantes who have met the criteria of Article 170 of the Criminal Code concerning violence or Article 351 of the Criminal Code concerning assault must be followed up with established legal provisions, in order to create criminal prosecution, legal certainty, and justice for the victims. (b) Vigilantes have an impact on the law no longer functioning as it is in Indonesia and are contrary to the theory of the rule of law. Taking action alone can have a negative impact on the victims, both those who suffer minor or serious injuries, physical disabilities, mental disabilities, and death. Therefore, to achieve law enforcement, it is necessary to strengthen the law that should be for everyone. So that they can understand the difference between their rights and obligations, and law enforcement agencies need to improve their skills in enforcing the existing law.